Krüppel-like factor 2 promotes cell proliferation in hepatocellular carcinoma through up-regulation of c-myc. Issue 1 (2nd January 2016) - Zou, Kailin; Lu, Xiaojie; Ye, Kun; Wang, Chunmei; You, Tiangeng; Chen, Jinlian
ABSTRACT: Members of krüppel-like factor family have been shown to play critical roles in the development, metabolism and tumorigenesis. Our previous study demonstrated that up-regulationupregulation of KLF2 in livers from obese mice could promote hepatosteatosis. However, little is known about its effects in hepatocellular carcinogenesis. In the present study, we found that mRNA and protein expression of KLF2 was increased in primary HCC, when compared with that in adjacent normal liver. In vitro studies further showed that enforced overexpression of KLF2 expression enhanced, while its knockdown inhibited cell proliferation and invasion. At the molecular level, c-myc was a direct transcriptional target of KLF2 and a KLF2-binding site in the c-myc promoter bound specifically to KLF2 protein. Indeed, ablation of c-myc largely attenuated the proliferative roles of KLF2 in HCC cells. Therefore, our data highlight an important role for KLF2/c-myc pathway in HCC development and progression.